Blinding eye disease in Western Australia: perspectives on data integration - Clark, Antony (Curtin University, 2014)
This thesis explores the utility of linked hospital administrative data for evaluating blinding eye diseases and the eye care provided for them in Western Australia. Alternative data sources and methodologies that complement linked data methods were explored. Areas of study were complications of cataract surgery, the epidemiology of blindness, diabetic retinopathy screening and management, causes of vision loss in remote Aboriginals, and the safety of intravitreal anti-vascular endothelial growth factors in age-related macular degeneration.